ANALYSING THE CHARACTERISTICS OF A PAIR TALK ON AN EDITING TASK ON TWO INTERMEDIATE INDONESIAN LEARNERS OF ENGLISH - Risa Fitria (Universitas Islam Negeri Banda Aceh, 2016)
Recent studies have paid attention to peer interaction as a means of second language (L2) learning. Interaction among learners in carrying out task is believed to mediate the process of L2 learning. The study therefore observed the nature of a pair talk in an interaction while completing a grammar task. The interaction was recorded and analysed by using language related episodes (LRE) in terms of form, lexicality, and mechanism. LRE was used in order to understand the characteristics of a pair talk at homogenous (intermediate-intermediate) level and to examine the participants’ accuracy in completing the task. The results suggest that even though the pair solved the questions in the task using form-focused LRE (F-LRE) and resolved the task interactively, they were not able to make correct decisions over grammar errors.